(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
Researching performance audits according to the dimensions of financial sustainability in light of the scarcity of resources and economic and social transformations in the business environment is of utmost importance in the non-profit non-governmental organizations in achieving the goals and correct the path and address deviations, and help them in improving the outputs of processes and associated procedures and capacity The research was based on the hypothesis that the existence of a performance audit program in accordance with the dimensions of financial sustainability leads to the measurement of the commitment of the Olympic Committee. National Iraqi indicators of financial sustainability of the dimension of revenue in order to improve performance and achieve financial sustainability. The researchers sought to employ the indicators of financial sustainability in the preparation of a proposed performance audit program for the Iraqi National Olympic Committee. The researchers reached a number of conclusions, the most important of which is that the study of financial sustainability and its indicators and the integration of these indicators with the performance audit indicators according to the dimensions of financial sustainability will improve performance and ensure financial sustainability in (non-profit) non-governmental organizations. The existence of a program and indicators of performance auditing in accordance with the dimensions of financial sustainability for non-governmental organizations and the Iraqi National Olympic Committee accredited by the Federal Audit Bureau in Iraq.